2021
DOI: 10.1097/md.0000000000024266
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of organs at risk in 5 different radiotherapy plans in patients with preoperatively irradiated rectal cancer

Abstract: Background: Intensity-modulated radiotherapy (IMRT) is a widely used irradiation technique in rectal cancer patients. We aimed to compare 4 different IMRT plans with 3-dimensional conformal radiotherapy (3D-CRT) considering organs at risk (OARs) in patients with rectal carcinoma. Methods: This retrospective study included 27 rectal cancer patients who were irradiated preoperatively between January 2016 and December 2018. Five different plans (4-field 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Consistently to previously reported experiences [23], the type of technique was significantly correlated to the development of toxicity events (p-value of 0.03). Also for the D 98% of the wall of the low anorectum, a statistical significance correlation was found (p-value of 0.043).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistently to previously reported experiences [23], the type of technique was significantly correlated to the development of toxicity events (p-value of 0.03). Also for the D 98% of the wall of the low anorectum, a statistical significance correlation was found (p-value of 0.043).…”
Section: Discussionsupporting
confidence: 89%
“…Buettner et al showed that the fraction of the circumference of the rectal wall irradiated at high doses is specifically important. Krol et al confirmed that less exposure of the rectal wall to intermediate or high doses of radiations, leads to fewer changes and complications [16,[23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…We found that the rectal wall can be an important DVH structure. Lower doses to the rectal wall were associated with lower numbers of acute and late AEs, similar to previous studies [31][32][33][34]. Many studies reported an increased risk of late rectal bleeding when the rectum received higher RT doses [35][36][37].…”
Section: Discussionsupporting
confidence: 85%
“…In our dosimetric study we compared the standard and traditionally used 3D-CRT technique with VMAT and HT for patients with locally advanced rectal cancer treated neoadjuvantly. In the literature, there are studies comparing different IMRT techniques with 3D-CRT, as well as with each other but no study has been published comparing 3D-CRT, VMAT, and HT techniques at the same time [14][15][16][17][18][19]. Traditionally, 3D-CRT has been used for LARC targeting the primary tumor and mesorectum as well as lymph nodes.…”
Section: Discussionmentioning
confidence: 99%